La France ou l’Italie ? Regards allemands sur les escaliers d’honneur (1700-1750) - Matthieu Lett (Bulletin du Centre de Recherche du Château de Versailles, 2022)
Using the example of the great staircase, one of the most important ceremonial rooms in palatial buildings in the early modern period, this article aims to investigate clients’ attitudes in relation to France and Italy in the Holy Roman Empire during the first half of the 18th century. This was partly a political phenomenon but it was also linked to travel and the theoretical treatises that may have contributed to the formation of Germanic architectural culture through the prism of these two countries. Some significant cases are analysed from manuscript and printed sources, and in particular the key role of the texts of Leonhard Christoph Sturm. Between 1700 and 1750, reference to France and Italy declined in the Empire.